Framing a 'Climate Change Frontier': International News Media Coverage Surrounding Natural Resource Development in Greenland. (August 2017) - Davies, William; Wright, Samuel; Van Alstine, James
News media helps shape the discourse around natural resource issues, especially rapidly emerging developments such as those taking place in the Arctic. Whilst the relationship between media and audience is complex, news media contributes towards setting the tone and expectations for the burgeoning number of stakeholders engaging with the Arctic, especially in the case of Greenland. This study undertakes a thematic analysis of English-language news media coverage surrounding natural resource development in Greenland to explore how the issue is framed. Five media frames are identified: an emerging resource frontier; the warming Arctic; high-risk activity; geopolitical Greenland; and vulnerable traditional societies. An overarching frame is present within the coverage, one which depicts Greenland as 'a climate change frontier', facing 'uncertainties in the face of rapid change'. Media portrayals of a close-knit relationship between a warming climate and a rush for natural resources in Greenland could be problematic for several reasons, namely the disparity between actual resource development taking place and an overemphasis on increased economic development following increased warming.